2020
DOI: 10.3389/fphar.2020.00551
|View full text |Cite
|
Sign up to set email alerts
|

Model-Informed Precision Dosing of Vancomycin in Hospitalized Children: Implementation and Adoption at an Academic Children’s Hospital

Abstract: Background: Model-informed precision dosing (MIPD) can serve as a powerful tool during therapeutic drug monitoring (TDM) to help individualize dosing in populations with large pharmacokinetic variation. Yet, adoption of MIPD in the clinical setting has been limited. Overcoming technologic hurdles that allow access to MIPD at the point-of-care and placing it in the hands of clinical specialists focused on medication dosing may encourage adoption. Objective: To describe the hospital implementation and usage of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 54 publications
(73 reference statements)
0
42
0
Order By: Relevance
“…However, recent advances in health care technology have fostered the development of more user‐friendly BF dosing support software 27 . Adoption of BF approaches in clinical care has also been facilitated through integration of dosing support software within the EHR, which allows access within the clinical workflow of providers and supports automatic transmission relevant patient data (ie, age, serum creatinine, dose and drug concentration history, serum creatinine) 17 . We recently integrated within our EHR (Epic Systems, Verona, Wisconsin) a commercially available cloud‐based web app (InsightRx, San Francisco, CA) that supports BF dosing and which we now use to estimate AUC 24 in all patients with CF receiving tobramycin at our center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent advances in health care technology have fostered the development of more user‐friendly BF dosing support software 27 . Adoption of BF approaches in clinical care has also been facilitated through integration of dosing support software within the EHR, which allows access within the clinical workflow of providers and supports automatic transmission relevant patient data (ie, age, serum creatinine, dose and drug concentration history, serum creatinine) 17 . We recently integrated within our EHR (Epic Systems, Verona, Wisconsin) a commercially available cloud‐based web app (InsightRx, San Francisco, CA) that supports BF dosing and which we now use to estimate AUC 24 in all patients with CF receiving tobramycin at our center.…”
Section: Discussionmentioning
confidence: 99%
“…The BF approach applies a population pharmacokinetic model as a Bayesian prior and integrates information known about the patient (eg, age, weight, renal function, drug concentrations) to predict the individual pharmacokinetics of a patient, which are then used to estimate AUC 24 . Recent advances in health care technology now offer the opportunity to implement BF approaches in clinical care 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, gentamicin model-based dosing in neonates and infants (neoGent) utilized a freely available MIPD tool which aids gentamicin TDM ( 76 ). The integration of a MIPD tool within the EHR can facilitate the adoption of precision dosing in routine clinical care ( 77 ). Kantasiripitak et al evaluated 10 MIPD software tools and they concluded that improvements should still be made concerning EHR integration, standardization of software and model validation strategies, and prospective evidence for the software tools' clinical and cost benefits ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…To fully exploit the potential benefits of MIPD, the tools must be implemented in an easy-to-use framework for the team of healthcare providers. Importantly, the role of clinical pharmacists is considered as a success factor to implement MIPD ( 77 ). As suggested by Keizer et al, the struggles of MIPD from bench-to-bedside involves the many workflow steps as described in Figure 1 ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic (PK) models have been brought to the point of care, aided by development and deployment of software tools that allow clinicians to estimate their patients’ PK parameters and simulate dosing regimens 1–3 . Preliminary studies suggest that this model‐informed precision dosing (MIPD) facilitates attainment of therapeutic targets, reduces drug‐induced adverse events, and improves clinical outcomes 4–6 .…”
mentioning
confidence: 99%